Effect of Pediatric Integrative Manual Therapy, a Novel Mobilization with Facilitation Movement Technique, on Congenital Muscular Torticollis after Cervical Rotation and Head angle : A Case Report - 송승혁; 황규정; 서태규; 김재등; 황원정 (대한정형도수물리치료학회지, 2023)
Background: Congenital muscular torticollis results in reduced head mobility, such as cervical rotation, due to the abnormal size and contraction of the sternocleidomastoid muscle. Korea Pediatric integrative manual therapy and stretching are recommended to improve head rotation upper cervical spine mobility. Therefore, in this study, the effect of the new PIMT was investigated. Methods: The patient is a 3.5 month-old diagnosed with congenital muscular torticollis (CMT). Due to the limitation of head rotation and cervical spine rotation and flexion mobility, the child visited a rehabilitation center and after diagnosis, Pediatric integrative manual therapy (PIMT) treatment was performed five times a week for a total of 15 weeks. The child's head rotation and flexion limitation and plagiocephaly were evaluated. Results: In conclusion, this study shows that compared to other treatments, PIMT approach is a more effective treatment for improving head rotation and cervical limitation for range of motion in CMT infants. Conclusion: PIMT approach was effective in improving cervical rotation and Head lateral flexion mobility and plagiocephaly in CMT patients.